Clinical Outcomes in Persons Coinfected With Human Immunodeficiency Virus and Hepatitis C Virus: Impact of Hepatitis C Virus Treatment. (2nd July 2019) - Mocroft, Amanda; Lundgren, Jens; Gerstoft, Jan; Rasmussen, Line D; Bhagani, Sanjay; Aho, Inka; Pradier, Christian; Bogner, Johannes R; Mussini, Christina; Uberti Foppa, Caterina; Maltez, Fernando; Laguno, Montse; et al.
Abstract: Background: A hepatitis C (HCV) cure is associated with changes in lipids and inflammatory biomarkers, but its impact on clinical endpoints among treated human immunodeficiency virus (HIV)/HCV coinfected persons is unclear. Methods: People living with HIV from EuroSIDA with a known HCV status after January 2001 were classified into strata based on time-updated HCV RNA measurements and HCV treatment, as either HCV antibody–negative; spontaneously resolved HCV; chronic, untreated HCV; cured HCV (HCV RNA–negative); or HCV treatment failures (HCV RNA–positive). Poisson regression was used to compare incidence rates between HCV groups for end-stage liver disease (ESLD; including hepatocellular carcinoma [HCC]), non–acquired immunodeficiency virus defining malignancy (NADM; excluding HCC), and cardiovascular disease (CVD). Results: There were 16 618 persons included (median follow-up 8.3 years, interquartile range 3.1–13.7). There were 887 CVD, 902 NADM, and 436 ESLD events; crude incidence rates/1000 person-years follow-up were 6.4 (95% confidence interval [CI] 6.0–6.9) for CVD, 6.5 (95% CI 6.1–6.9) for NADM, and 3.1 (95% CI 2.8–3.4) for ESLD. After adjustment, there were no differences in incidence rates of NADM or CVD across the 5 groups. HCV-negative individuals (adjusted incidence rate ratio [aIRR] 0.22, 95% CI 0.14–0.34) and those with spontaneous clearance (aIRR 0.61, 95% CI 0.36–1.02) had reduced rates of ESLD compared to cured individuals. Persons with chronic, untreated HCV infections (aIRR 1.47, 95% CI 1.02–2.13) or treatment failure (aIRR 1.80, 95% CI 1.22–2.66) had significantly raised rates of ESLD, compared to those who were cured. Conclusions: Incidences of NADM or CVD were independent of HCV group, whereas those cured had substantially lower incidences of ESLD, underlining the importance of successful HCV treatment for reducing ESLD. Abstract : Hepatitis C virus (HCV) treatment impacts lipid and inflammatory markers in persons with HCV and human immunodeficiency virus. Results showed no differences in non–acquired immunodeficiency virus defining malignancy or cardiovascular disease between those with chronic HCV and prior HCV.